Cow, Sheep and Goat Hematological Parameters: Comparative Studies Between Automated Analyzer and Manual Methods - Ibraheem E. Ibrhim (Kufa Journal for Veterinary Medical Sciences, 2014)
This study was designed to compare the values of some hematological parameters in some farm animals estimated by Automated Analyzer and Manual method estimation. The blood samples were collected randomly from five animals from each of the following species; cow, sheep and goat (5 sample for each). The blood samples were divided into two parts, the first were used for manual estimation and the second was analyzed by automated hematology analyzer.. The blood profile showed no significant variation ( p; < 0.05) in White Blood Cells (WBC), Red Blood cells (RBC) between all animals groups. The results of this study showed significant differences that revealed decreased in the Hemoglobin (HB) (20 g/dl) and (20.5g/dl) in cow and sheep respectively and increased of Package Cell Volume(PCV)  (33.33%) . However, goat revealed significant increase in Package Cell Volume  and Hemoglobin (6.04%and 21g/dl).